2014
DOI: 10.1016/j.colsurfa.2014.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Gels under stress: The origins of delayed collapse

Abstract: Attractive colloidal particles can form a disordered elastic solid or gel when quenched into a twophase region, if the volume fraction is sufficiently large. When the interactions are comparable to thermal energies the stress-bearing network within the gel restructures over time as individual particle bonds break and reform. Typically, under gravity such weak gels show a prolonged period of either no or very slow settling, followed by a sudden and rapid collapse -a phenomenon known as delayed collapse. The lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
(74 reference statements)
4
27
0
Order By: Relevance
“…The most common and ultimate metric characterizing the macroscopic feature of the collapse process is the time evolution of the height profile, h(t) of a gel. Measurements of h(t) are used to determine the characteristic timescale of the process, t d , and to quantify observed power-law or exponential decays of height profiles (Weeks et al 2000;Teece et al 2014;Harich et al 2016). The collapse dynamics of colloidal dispersions with long-ranged attractions, relative to the primary particle radius, are relatively well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common and ultimate metric characterizing the macroscopic feature of the collapse process is the time evolution of the height profile, h(t) of a gel. Measurements of h(t) are used to determine the characteristic timescale of the process, t d , and to quantify observed power-law or exponential decays of height profiles (Weeks et al 2000;Teece et al 2014;Harich et al 2016). The collapse dynamics of colloidal dispersions with long-ranged attractions, relative to the primary particle radius, are relatively well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Careful confocal microscopy studies of the association and dissociation processes of individual particles and gel strands in the network structure have also shown that there is a direct link between the macroscopic mean delay time t d and the lifetime of an individual colloid-colloid bond (Gopalakrishnan et al 2006;Teece et al 2014). As a result simple phenomenological models have been developed that describe the collapse process in terms of a number of sticky inter-particle bonds undergoing sequential activated bond breaking and leading to a loss of network integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable dynamic control of the aggregation process has been realised in phase-separating colloidal suspensions, which may afford a kinetically trapped gel material before coalescing into a more compact equilibrium arrangement. 107 The mechanism of degelation may also exhibit unexpected complexity. A common observation is that the temperature of the gel-sol transition exceeds Tgel, due to the kinetic stability of the aggregate state.…”
Section: Switchable Gelationmentioning
confidence: 99%
“…1,2 Examples of such consumer products include fabric enhancers, cosmetics, and shampoos. 3 In many of these applications, the dispersed phase has a higher density than the continuous phase. Therefore, sedimentation of the dispersed phase may occur due to gravity.…”
Section: Introductionmentioning
confidence: 99%